Análise de variabilidades, conflitos de metas e desperdícios em operações integradas a partir do método de análise de ressonância funcional : um estudo do tempo de permanência na internação hospitalar - Lando, Felipe (2018)
Complex sociotechnical systems are those where humans need to handle with variabilities and adapt their operations to maintain acceptable levels of efficiency and thoroughness. Hospitals of complete care are examples of such systems, due to its necessities of highly specialized work force, the use of intensive wealth and technology. These organizations are characterized by their external and internal variabilities. The external variabilities are, in a hospital, the climate changes, the unknown diseases and the uncertainty in the quantity and necessities of the incoming patients. In the other side, the internal variabilities are related to the resource management, the time and results pressure and the conflicting goals. Due to that, losses are created and reflect on efficiency and thoroughness performances. The literature has driven researches in sociotechnical systems seeking to analyze their activities. The FRAM method is being used as a tool to model and analyze those activities. In this way, the aim of this research is to characterize a complex sociotechnical system in relation to its variabilities, conflicting goals, and wastes in the activities and its relations with the system’s integrated operations. To do that, we took as the analyzed object, the average length of stay of patients in the Brazilian public health (SUS) hospitalization of a University hospital. The beginning of the analysis is the discharge of a patient in an entry unit to the hospitalization. The end of the analysis is the final discharge of the patient and the preparing of its bed to another patient. The hospitalization system seems to be good to a study that aims to analyze variabilities, because it represents a significant amount of the challenges of a hospital and it is inside the boundaries of a tractable study. The explorative and qualitative inquiry method and the FRAM modeling allowed the identification of a 66-function model that represents the hospitalization system. From this model, we selected three instantiations for the further analysis. These instantiations were selected because represented a significative amount of wastes when analyzed through the lens of Lean Systems. The model and instantiations generated an inventory of wastes, ETTOs and variabilities. The analysis was conducted in a way to identify were decision-makers must choose between production and protection. These decision points are characterized by presenting resonant variabilities in the system, which generates wastes in other functions (e.g. waiting, inappropriate processing, etc.). Therefore, looking for Integrated Operations, we tried to identify points of the system’s structure that could influence those variabilities and wastes. The main theoretical contribution of this research is the proposition of a method to investigate wastes, ETTOs and variabilities associated to functions in a FRAM modeling. We also propose a new approach of analyzing integrated operations in a FRAM modeling. In the same way, pragmatic contributions pointed out to the need of a better resource management in the hospital. This could make the system’s activities more efficient without interfering in its resilience. Future studies could reply this method in other contexts looking for validation. Deeping the data gathering in the researched hospital could result in better understanding of each essential function identified. Furthermore, replying this research in other Hospital could lead to recommendations in the contractual level of the Public Health Services (SUS).